Cleidocranial Dysplasia Case Report: Remodeling of Teeth as Aesthetic Restorative Treatment - Leonardo Fernandes da Cunha; Isabela Maria Caetano; Fernando Dalitz; Carla Castiglia Gonzaga; José Mondelli (Hindawi Limited, 2014)
Cleidocranial dysplasia (CCD), is an autosomal dominant disorder with a prevalence of 1 in 1,000,000 individuals. It is generally characterized by orofacial manifestations, including enamel hypoplasia, retained primary teeth, and impacted permanent and supernumerary teeth. The successful treatment involving a timing intervention (orthodontic-maxillofacial surgeons-restorative) is already described. However, the restorative treatment might improve the aesthetic final result in dentistry management for patients with cleidocranial dysplasia. Objective. Therefore, this clinical report presents a conservative restorative management (enamel microabrasion, dental bleaching, and direct composite resin) for aesthetic solution for a patient with CCD. Clinical Considerations. The cosmetic remodeling is a conservative, secure, and low cost therapy that can be associated with other procedures such as enamel microabrasion and dental bleaching to achieve optimal outcome. Additionally, the Golden Proportion can be used to guide dental remodeling to improve the harmony of the smile and the facial composition. Conclusions. Thus, dentists must know and be able to treat dental aesthetic problems in cleidocranial dysplasia patients. The intention of this paper is to describe a restorative approach with the cosmetic remodeling teeth (by grinding or addicting material) associated with enamel microabrasion and dental bleaching to reestablish the form, shape, and color of smile for patients with cleidocranial dysplasia.